1996
DOI: 10.1023/a:1016047816699
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The profound differences in SC lipid composition, organization and conformational properties attest that permeability alone is not a sufficiently sensitive marker to define barrier equivalence between cultures and human skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…All these differences were also detected in the previously examined HSEs . Additionally, HSEs developed by other groups or commercially available models also have a reduced SC free fatty acid content, a mainly hexagonal packing and generally show the presence of the LPP . It should be noted that the SC lipid properties of commercially available models were investigated several years ago.…”
Section: Discussionmentioning
confidence: 67%
“…All these differences were also detected in the previously examined HSEs . Additionally, HSEs developed by other groups or commercially available models also have a reduced SC free fatty acid content, a mainly hexagonal packing and generally show the presence of the LPP . It should be noted that the SC lipid properties of commercially available models were investigated several years ago.…”
Section: Discussionmentioning
confidence: 67%
“…These factors may be key elements for the decreased permeability barrier observed for LEMs . All HSEs developed so far have a reduced skin barrier function and altered FA content compared to human skin , suggesting that epidermal lipid metabolism is partially disturbed in all these models.…”
Section: Discussionmentioning
confidence: 99%
“…Mak et al demonstrated that de-epidermized dermis coupled with 1,25-dihydroxy vitamin D3 helps the barrier resemble that of human skin ( Mak et al, 1991 ). Even still, this model lacked covalently bound lipid lamellae that properly extruded into the regions between cells, which is a foundational part of the skin barrier ( Bouwstra et al, 1995 ; Kennedy et al, 1996 ). Following this, Boyce and Williams showed that adding palmitic acid, essential fatty acids, and antioxidants increased the synthesis of lipids and improved extrusion ( Boyce and Williams, 1993 ).…”
Section: Discussionmentioning
confidence: 99%